Unemployment benefits, food insecurity, and supplemental nutrition assistance program spending. Issue 2 (20th June 2022) - Fu, Wei; Huang, Chen; Liu, Feng
Abstract: This paper examines the effects of unemployment insurance (UI) expansions on household food insecurity in the United States using the Food Security Supplement to the Current Population Survey for 1999–2017. We exploit the plausibly exogenous variation in state maximum weekly UI benefits across states and over time. The two‐part model demonstrates that a $100 increase in state weekly UI benefits reduces the likelihood of food insecurity among UI‐eligible families by 5.6% and the severity of food insecurity conditional on being food insecure by 6.3%. We further present strong evidence of program substitution between UI and the Supplemental Nutrition Assistance Program (SNAP), which is the largest food assistance program with the stated goal of reducing food insecurity. Specifically, for every dollar spent on UI, 4–11 cents can be saved on SNAP, thereby reinforcing the social benefits of an UI expansion .